How Much Will Poverty Rise in Sub-Saharan Africa in 2020? - Montes, Jose; Silwal, Ani; Newhouse, David; Chen, Frances; Swindle, Rachel; Tian, Siwei (World Bank, Washington, DC, 2020)
The ongoing coronavirus pandemic is expected to drastically slow 2020 GDP per capita growth in Sub-Saharan Africa (SSA) by about 5 percentage points compared to pre-pandemic forecasts. This note presents results from an analysis of a comprehensive database of surveys from 45 of 48 SSA countries to examine the effects of the project fall in growth on poverty in the region. An additional 26 million people in SSA, and as much as 58 million, may fall into extreme poverty defined by the international poverty line of 1.90 US Dollars per day in 2011 PPP. The poverty rate for SSA will likely increase more than two percentage points, setting back poverty reduction in the region by about 5 years.